Ventromedial frontal lobe damage affects interpretation, not exploration, of emotional facial expressions. (April 2019) - Vaidya, Avinash R.; Fellows, Lesley K.
Abstract: Recognizing and distinguishing the emotional states of those around us is crucial for adaptive social behavior. Previous work has shown that damage to the ventromedial frontal lobe (VMF) impairs recognition of subtle emotional facial expressions and affects fixation patterns to face stimuli. However, whether this relates to deficits in acquiring or interpreting facial expression information remains unclear. We tested 37 patients with frontal lobe damage, including 17 subjects with VMF lesions, in a series of emotion recognition tasks with different gaze manipulations. Subjects were asked to rate neutral, subtle and extreme emotional expressions while freely examining faces, while instructed to look only at the eyes, and in a gaze-contingent condition that required top-down direction of eye movements to reveal the stimulus. People with VMF damage were worse at detecting subtle disgust during free viewing and confused extreme emotional expressions more than healthy controls. However, fixation patterns did not differ systematically between groups during free or gaze-contingent viewing conditions. Moreover, instruction to fixate only the eyes did not improve the performance of VMF damaged subjects. These data argue that VMF is not necessary for normal fixations to emotional face stimuli, and that impairments in emotion recognition after VMF damage do not stem from impaired information gathering, as indexed by patterns of fixation.